2009
DOI: 10.1002/clc.20471
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Characteristics of the Coronary Segment Proximal to the Culprit Lesion in Stable and Unstable Patients

Abstract: Background: Identifying vulnerable plaque is important for preventing an acute coronary event. The present study examined the relationship between the clinical presentation of coronary artery disease and the plaque characteristics of nonculprit segment assessed by virtual histology intravascular ultrasound (VH-IVUS Results: ACS patients showed significantly higher ratio of dense calcium (7.9%±1.0% versus 5.0%±0.9%, p = 0.03) and necrotic core plaque (13.7%±1.1% versus 8.6%±1.1%, p = 0.001) compared with SA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…In addition, fibroatheromas that became more stable in appearance over the time tended to be located more distally, whereas fibroatheromas that did not change or that became unstable tended to be located more proximally in the coronary tree . Similar indications derive from the study of Nakamura et al: they showed that thin‐cap fibroatheromas were more common in ACS patients compared with stable patients (64.6% vs. 35.7%, P = 0.006) .…”
Section: How To Consider Nonculprit Lesions?supporting
confidence: 53%
“…In addition, fibroatheromas that became more stable in appearance over the time tended to be located more distally, whereas fibroatheromas that did not change or that became unstable tended to be located more proximally in the coronary tree . Similar indications derive from the study of Nakamura et al: they showed that thin‐cap fibroatheromas were more common in ACS patients compared with stable patients (64.6% vs. 35.7%, P = 0.006) .…”
Section: How To Consider Nonculprit Lesions?supporting
confidence: 53%
“…25) Furthermore, a previous report by IVUS also reported that ACS patients showed a significantly higher ratio of NC plaque compared with SAP patients, and VH-IVUS-derived TCFA was more frequently observed in ACS patients compared with SAP patients. 26) In the present study, the ACS group had significantly more %NC and NC volume and less %Fibrous than the SAP group. Additionally, %CD163-positive macrophages were positively correlated with %NC and negatively correlated with %Fibrous in culprit plaque.…”
Section: Difference In Ivus and Vh-ivus Parameters Between Acssupporting
confidence: 47%
“…The prevalence of TCFA in culprit lesions is still controversial, ranging from 21.6 to 60.3% of cases . These results have depend on the population included in each study and the criteria for calling a plaque a TCFA . In the present study, the overall prevalence of iMAP‐derived TCFA was 32.6%, with a greater frequency in culprit lesions (39%) compared to non‐culprit lesions (19%).…”
Section: Discussionmentioning
confidence: 59%